Tumor Microenvironment Characterization for Assessment of Recurrence and Survival Outcome in Gastric Cancer to Predict Chemotherapy and Immunotherapy Response - Chen, Yan; Sun, Zepang; Wan, Li; Chen, Hongzhuan; Xi, Tieju; Jiang, Yuming (Frontiers in Immunology, 2022)
Background: The tumor microenvironment (TME) is crucial in tumor recurrence, prognosis, and therapeutic responses. We comprehensively investigated the TME characterization associated with relapse and survival outcome of gastric cancer (GC) to predict chemotherapy and immunotherapy response. Methods: A total of 2456 GC patients with complete gene-expression data and clinical annotations from twelve cohorts were included. The TME characteristics were evaluated using three proposed computational algorithms. We then developed a TME-classifier, a TME-cluster and a TME-based risk score for assessment of tumor recurrence and prognosis in patients with GC to predict chemotherapy and immunotherapy response. Results: Patients with tumor recurrence presented with inactive immunogenicity, including high infiltration of tumor-associated stromal cells, low infiltration of tumor-associated immunoactivated lymphocytes, high stromal score, and low immune score. The TME-classifier of 4 subtypes with distinct clinicopathology, genomic, and molecular characteristics was significantly associated with tumor recurrence (P=0.002), disease-free survival (DFS, P<0.001) and overall survival (OS, P<0.001) adjusted by confounding variables in 1193 stage I-III GC patients who underwent potential radical surgery. The TME cluster and TME-based risk score can also predict DFS (P<0.001) and OS (P<0.001). More importantly, we found that patients in the TMEclassifier-A, TMEclassifier-C, and TMEclassifier-D group benefited from adjuvant chemotherapy, and patients in the TMEclassifier-B group without chemotherapy benefit responded best to pembrolizumab treatment (PD-1 inhibitor), followed by patients in the TMEclassifier-A, while patients in C and D group of the TMEclassifier responded poorly to immunotherapy. Conclusion: We determined that TME characterization is significantly associated with tumor recurrence and prognosis. The TME-classifier we proposed can potentially guide individualized chemotherapy and immunotherapy decision-making.